STUDY OF MORPHOLOGY OF CARBON NANOTUBES PRODUCED BY MICROWAVE SYNTHESIS FOR COMPOSITE ELECTRIC HEATER WITH TEMPERATURE SELF-REGULATION EFFECT - Shchegolkov, Alexander V.; Orlova, Natalia V.; Shchegolkov, Aleksey V.; Chumak, Maksim A. (ChemChemTech, 2025)
The paper presents studies of carbon nanotubes (CNTs) synthesised by microwave method, which are intended for the creation of functional composites - possessing the effect of self-regulation of temperature. Microwave technology allows the synthesis of CNTs, which differ in morphological characteristics, as well as the presence of metallisation of the CNT surface. Different composition ratios based on graphite and ferrocene were used for CNT synthesis. The obtained CNT samples were characterised by CR spectroscopy, SEM and X-ray diffraction analysis. It is shown that combinations of ferrocene and graphite in the ratio of 3:1; 4:1; 5:1 and 6:1 result in the formation of different morphological structure of CNTs, which has a high level of diversity and allows to carry out effective modification of elastic matrices with giving the composite electrically conductive properties. The diameter of CNTs is in the range from 30 to 60 nm and there are Fe3C cogenite particles on the surface of CNTs obtained by synthesis with the ratio of ferrocene to graphite 6:1. Metallisation of the CNT surface layer significantly improves the thermophysical characteristics (thermal conductivity and diffusivity) of both the CNTs themselves and the composites obtained on their basis, which affects their heat release and allows them to operate with higher values of the self-regulation temperature at the same value of the supply voltage. The synthesis is characterised by a microwave power of 700 W. Microwave synthesis is a fast method for obtaining CNTs (synthesis time 10 s) and can be used for directed synthesis of CNTs, which are intended for modification of polymers and creation of conductive composites, which can be the basis of electric heaters with the effect of temperature self-regulation. For citation: Shchegolkov A.V., Orlova N.V., Shchegolkov A.V., Chumak M.A. Study of morphology of carbon nanotubes produced by microwave synthesis for composite electric heater with temperature self-regulation effect. ChemChemTech [Izv. Vyssh. Uchebn. Zaved. Khim. Khim. Tekhnol.]. 2025. V. 68. N 2. P. 70-78. DOI: 10.6060/ivkkt.20256802.7157.